The protective effects of a synthetic geranyl acetophenone in a cellular model of TNF-α-induced pulmonary epithelial barrier dysfunction - Tee, Yee Sim; Harith, Hanis Hazeera; Tham, Chau Ling; Md Hashim, Nur Fariesha; Shaari, Khozirah; Sulaiman, Mohd Roslan; Israf Ali, Daud Ahmad (MDPI, 2018)
Alveolar epithelial barrier dysfunction contributes to lung edema and can lead to acute lung injury (ALI). The features include increased epithelial permeability, upregulation of inflammatory mediators and downregulation of junctional complex molecules; these changes are often induced by inflammation. tHGA is an acetophenone analogue with therapeutic potential in asthma. Its therapeutic potential in ALI is presently unknown. Herein, the effects of tHGA on epithelial barrier dysfunction were determined in TNF-α-induced human alveolar epithelial cells. The anti-inflammatory properties of tHGA were assessed by monocyte adhesion assay and analysis of MCP-1 and ICAM-1 expression. The epithelial barrier function was assessed by paracellular permeability and transepithelial electrical resistance (TEER) assays, and analysis of junctional complex molecules expression. To elucidate the mechanism of action, the effects of tHGA on the NF-κB and MAPK pathways were determined. Gene and protein expression were analyzed by RT-PCR and Western blotting or ELISA, respectively. tHGA suppressed leukocyte adhesion to TNF-α-induced epithelium and reduced MCP-1 and ICAM-1 gene expression and secretion. tHGA also increased TEER readings, reduced epithelial permeability and enhanced expression of junctional complex molecules (zona occludens-1, occludin and E-cadherin) in TNF-α-induced cells. Correspondingly, the NF-κB, ERK and p38 MAPK pathways were also inhibited by tHGA. These findings suggest that tHGA is able to preserve alveolar epithelial barrier function in response to acute inflammation, via its anti-inflammatory activity and stabilization of epithelial barrier integrity, mediated by NF-κB, ERK and p38 MAPK signaling.